2015
DOI: 10.1088/1367-2630/17/4/043003
|View full text |Cite
|
Sign up to set email alerts
|

Gibbs-preserving maps outperform thermal operations in the quantum regime

Abstract: In this brief paper, we compare two frameworks for characterizing possible operations in quantum thermodynamics. One framework considers thermal operations-unitaries which conserve energy. The other framework considers all maps which preserve the Gibbs state at a given temperature. Thermal operations preserve the Gibbs state; hence a natural question which arises is whether the two frameworks are equivalent. Classically, this is true-Gibbs-preserving maps are no more powerful than thermal operations. Here, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
135
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(138 citation statements)
references
References 31 publications
(31 reference statements)
1
135
0
Order By: Relevance
“…The most general quantum operations that fulfill Eq. (4) are known as Gibbs-preserving operations, and it has been shown that such operations can create coherence [55]. Here, we contribute to this discussion by introducing the set of Gibbs-preserving SIO, and giving a full solution for the mixed-state conversion problem on a single qubit.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…The most general quantum operations that fulfill Eq. (4) are known as Gibbs-preserving operations, and it has been shown that such operations can create coherence [55]. Here, we contribute to this discussion by introducing the set of Gibbs-preserving SIO, and giving a full solution for the mixed-state conversion problem on a single qubit.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…Another theorem used in [97] and other studies [98] of quantum thermodynamics is the channelstate duality or Choi-Jamio lkowski isomorphism. It says that there is a state ρ Φ isomorphic to every CPTP map Φ, given by…”
Section: Three Theorems Involving Cptp Mapsmentioning
confidence: 99%
“…(34). We note that these theorems are often implicitly assumed while discussing quantum thermodynamics from the standpoint of CPTP maps, see [98,100,101] for examples.…”
Section: Three Theorems Involving Cptp Mapsmentioning
confidence: 99%
“…The literature about thermodynamic resource theories has exploded recently. Since the first draft of the present paper was released, for example, coherences [29,30] and correlations have been explored [31], connections have been drawn to fluctuation relations [32][33][34], and free operations have been generalized [23].…”
Section: B Generalized Thermodynamic Resource Theoriesmentioning
confidence: 99%
“…Nonequilibrium states' values have been quantified with a family of equivalent resource theories, each associated with an inverse temperature β of the bath [18][19][20][21][22][23]. We call these resource theories Helmholtz theories, Many experiments involve baths other than heat baths, involve interactions other heat exchanges, and are characterized by free energies other than the Helmholtz free energy.…”
Section: Introductionmentioning
confidence: 99%